Tingkat Kesukaan Dan Karakteristik Kimia Kue Semprong Dari Tepung Ubi Banggai (Dioscorea sp) Dan Tepung Terigu - Sheren L. Satolom; Teltje Koapaha; Jan R. Assa (COCOS, 2019)
Abstract Banggai Regency is one of the regencies in Central Sulawesi Province that has a natural beauty and diverse natural resources, including local foodstuffs, one of them is proud cassava (Dioscorea sp.). Sweet potato (Dioscorea sp) or often called uwi is one of the many species of the genus Dioscoreaceae. Dioscoreaceae has potential as a food source because it contains a high amount of carbohydrates. Sweet potato processing is a form of flour that is more resistant to storage, easy to mix, and is more practical and easy to use for advanced processing such as making semprong cakes. The semprong cake is one of the traditional pastries and is loved by the people of Indonesia. The main ingredients for making this semprong cake are wheat flour, coconut milk, eggs, sugar and cinnamon as flavoring ingredients. This study aims to determine the most appropriate proportion of proud sweet potato flour and wheat flour, based on organoleptic testing of semprong cakes and knowing the chemical characteristics of semprong cakes. This study used a Completely Randomized Design (CRD) with Treatments A (100% Banggai Sweet Potato Flour), B (75% Banggai Sweet Potato Flour: 25% Wheat Flour), C (50% Proud Cassava Flour: 50% Wheat Flour), D (D) 25% Banggai Sweet Potato Flour: 75% Flour) and E (100% Flour). The preferred organoleptic test for the semprong cake in terms of color, taste, aroma and texture is the D treatment (75% wheat flour: 25% proud yam flour). The results of the chemical analysis of semprong cakes for water content ranged between 1.78% - 2.99%, ash content 1.37% - 2.10%, fat content 22.74% - 23.60%, protein content 7.20 % - 7.62%, and carbohydrate content 65.18 - 65.67%. Keywords : Semprong Cake, Banggai Yam Flour and Wheat Flour